SISTEM PENDUKUNG KEPUTUSAN MOBILE KETAHANAN PANGAN BERBASIS ANALITIK HARGA DAN DISTRIBUSI DI KABUPATEN LAMONGAN - Misbahul Musthofah, Moh.; Vita Via, Yisti (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Regional food security requires an information system that integrates price, stock, distribution, field report, and early-warning data into a unified decision-making workflow. This study develops PanganKu as a mobile decision support system prototype for food security monitoring in Lamongan Regency. The research used a three-iteration prototyping approach covering system architecture design, functional requirement formulation, price-distribution analytics implementation, and system verification. Evaluation was conducted through black-box testing, algorithm unit testing, and calibrated simulation-based price scenarios. The system provides price and stock monitoring, simple price prediction, anomaly detection, geographic distance estimation, and preliminary surplus-deficit distribution recommendations. The results show that all functional test cases produced outputs consistent with expected results. Price scenario evaluation produced a mean absolute percentage error of 1.0% for stable commodities and 14.2% for volatile commodities. These results indicate consistent algorithm behavior in limited scenarios rather than market-level prediction accuracy. Operational implementation still requires official daily data, end-user testing, field validation, and structured load testing.